2015
DOI: 10.1080/10550887.2016.1107289
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of saccadic functions after dosing with methadone in opioid addicted individuals

Abstract: In the current experiment, we used the saccadometric test to study the effect of a single therapeutic dose of methadone on the integrity of cortico-subcortical brain functioning. In this prospective study, we used the Saccadometer System (Advanced Clinical Instrumentation, Cambridge, UK). The saccadometric test was performed before and 1.5 hours after methadone dosing. We analyzed the following saccadic parameters: latency, duration, amplitude, average and peak velocity, and processing performance (promptness)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The evidence, collected by inter alia authors of this paper, suggests that both opioid addicted and gambling addicted individuals can be characterized with higher levels of risk behavior in comparison to healthy people (Brevers et al, 2013;Gorzelańczyk et al, 2014). It has been shown that the administration of substitution drugs can reduce cravings for opioids and also decrease risky decision making among individuals addicted to opioids (Gorzelańczyk et al, 2014;Hu et al, 2019;Kriegler et al, 2019;Kelty et al, 2020).…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…The evidence, collected by inter alia authors of this paper, suggests that both opioid addicted and gambling addicted individuals can be characterized with higher levels of risk behavior in comparison to healthy people (Brevers et al, 2013;Gorzelańczyk et al, 2014). It has been shown that the administration of substitution drugs can reduce cravings for opioids and also decrease risky decision making among individuals addicted to opioids (Gorzelańczyk et al, 2014;Hu et al, 2019;Kriegler et al, 2019;Kelty et al, 2020).…”
Section: Introductionmentioning
confidence: 83%
“…It has been observed that the substitution drug (methadone) reduces the level of risky behavior in opioid addicts (Gorzelańczyk et al, 2014). It is interesting to see whether the decision-making strategy before administration of the substitution drug is similar in opioid addicts to the strategy in those who are addicted to gambling and whether the decisionmaking strategy after administration of the drug is similar to healthy individuals, which has been stated in inter alia: (King et al, 2015;Gallimberti et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations